Care burden, coping styles and involvement in care in mothers of autistic children in pandemic of COVID‐19 - Fateme Mohammad; Niloofar Sani; Khodayar Oshvandi; Seyedeh Zahra Masoumi; Salman Khazaei; Saeid Bashirian; Ensiyeh Jenabi; Majid Barati; Mohammad Rezaei; Seyed Reza Borzou (Wiley, 2022)
Abstract Aim The aim of the present study was to investigate the burden of care, coping styles and involvement in the care of mothers of autistic children in the pandemic of COVID‐19 in Iranian society. Design A cross‐sectional study. Methods A total of 134 mothers completed questionnaires online. Data were analysed by descriptive statistics (frequency, percentage, mean and standard deviation) and independent t‐test, ANOVA and multiple linear regressions. The significance level was considered p < .05. Result Findings of the study found that burden of care has a strong and direct correlation with involvement in care (p < .001, r = .78) and strongly and indirectly correlated with coping styles (p < .001, r = −.82). Variables of coping styles, involvement in care, mothers' occupation and number of children, age and functional level of autism can predict 81.27% of the variance in care burden in these mothers.